Совершенствование процессов преподавания и обучения через систему оценивания - Кучина, О. В. (My University, 2016)
This article presents new approaches to evaluation : using formative and summarizing evaluation with some developed criteria at the lesson; thoughts and conclusions about putting into practice some types of evaluation for motivation and activizing of cognitive students activity and improving the quality of teaching process.
Keywords: formative and summarizing evaluation; criteria of evaluation feed back